Developing Social Capital by the Gintingan Tradition in Jalancagak Community of Subang, West Java - Tita Nurmalasari (FISIP UIN SGD Bandung, 2021)
This study aimed to discover the history of the Gintingan Tradition and Social Capital of the people of Bunihayu Village, Jalancagak District, Subang Regency in the Gintingan tradition through three elements of social capital, namely trust, reciprocity, and community social networks. This research is qualitative with the case study method, the acquisition of data analyzed in the form of narratives from informants, not numbers. The collection of all data in this study was carried out utilizing observation, interviews, literature studies and documentation. Data analysis includes collecting all data, and reducing and classifying data to conclusions as a result of research. The Gintingan tradition shows the existence of social capital in society through three elements of social capital: the importance of mutual trust between the involved people alternately exchange kindness and donate to each other to help host. The people of Bunihayu Village also have an extensive social network to achieve common and individual goals. Some people who are not involved in the Gintingan Tradition reason that they do not want to take the risk of paying back what they receive if they carry out a celebration with the Gintingan Tradition, some do not participate because lack of interaction and social networking with other communities. Based on the results of the research that has been done, it cannot be determined when the gintingan tradition was first carried out by the people of Bunihayu Village, Jalancagak District, Subang Regency. The shape and purpose of the gintingan tradition have not changed. Still, things related to the gintingan tradition have changed, such as the invitation paper, the recording of guests who keep the stubs, and the form of the dish or buffet.